4CPS-117 Relationship between daily dose frequency and adherence in chronic myeloid leukaemia. (2nd March 2018) - Gil, S García; Casariego, GJ Nazco; Romero, MM Viña; Virginia, G; Alarcón, C; Piñero, M; García, J González; Nicolás, F Gutiérrez
Abstract : Background: Adherence to tyrosine-kinase inhibitors (TKIs) treatment is regarded as one of the mainstays of chronic myeloid leukaemia (CML). Purpose: To analyse the variability in the adherence to TKIs treatment of CML in the function of the prescribed drug and evaluate how pharmaceutical care can improve it. Material and methods: A prospective, multicentre and observational study from October 2014 to May 2015. Participants were patients diagnosed with CML who received treatment with TKIs. The study consists of two phases: observation phase to obtain initial vision of the adherence; and a second phase of intervention after 12 months, where pharmaceutical care was performed on non-adherent patients, and re-evaluation of adherence was carried out. Adherence was analysed by compilation of three indirect methods: MMAS8 self-questionnaire (8-item Morisky Medication-Adherence scale); the Simplified Scale for Adherence Problems (ESPA); and the dispensing record (DR) in the past 6 month (non-adherent: DR lower than 90%). The identification of a lack in adherence by any of the three methods, classified the patient as non-adherent. The study had been approved by the hospital's Ethical Committee (CEIC) and classified as EPA-SP by the Spanish Agency for Drugs and Health Products (AEMPS) with the LOH-IMA-2013–01 code. Patients were requested to sign an informed consent form prior to their inclusion. Results: One hundred and thirty patients were included, with an average age of 58.9 (20–90) years and 55.5% males. 63.8% of patients received treatment with imatinib, 24.6% nilotinib and 11.6% with dasatinib. Adherence in the observation phase was 68.4%, showing no differences in the adherence of the different treatments (p=0.67). After the intervention phase, the adherence was 82.9% (p=0.007). However, treatment subgroup analysis showed that adherence, after the intervention phase, only improved in those patients whose TKI was given once daily: imatinib 54.8% vs 81.9% (p=0.002); nilotinib 63.6% vs 78.5% (p=0, 156) and dasatinib 54.3% vs 86.7% (p=0.049). Conclusion: Our results suggest that pharmacist intervention in outpatient units improve adherence in patients with CML treated with TKIs. However, the adherence is only improved with the once-daily treatments of imatinib and dasatinib. No conflict of interest